Rancang Bangun Sistem Sortasi Cerdas Berbasis Pengolahan Citra Untuk Kopi Beras - Sandi Asmara; Warji . (PERTETA, 2010)
AbstractLampung Province is the largest producer of cassava in Indonesia. Cassava has a weakness that is easily damaged and could not be stored longer. To overcome this, there is a need of an effective drying process so that cassava can be processed into other materials of lower power use as well as its economic value. A hybrid drying system is one solution to resolve the issue. The purpose of this research is to study the performance of drying cassava chips by using a hybrid type of dryer rack. The process of drying cassava chips made using a three-stage treatments with three replicates with the input load of 30 kg of cassava chips. The results showed that the pattern of decline in water levels in each treatment is uneven. The time needed to dry cassava chips to reach the water content of 10% - 12% in the drying of materials using sunlight for 18 hours, using electrical energy for 16 hours and use the energy of sunlight and electricity for 12 hours. The higher temperatures produced the shorter the time required in the drying process. Electrical energy required for the drying process using electric energy was 91 440 kJ and drying using electrical energy and sunlight was 68600 kJ.Keywords: cassava chip, drying, dryer hybridDiterima: 13 Maret 2010; Disetujui: 17 Setember 2010